Phosphate adsorption and immobilization characteristics of three soils from southern Bahia, Brazil - Rosand, Percy Cabala; Wild, Alan (Pesquisa Agropecuaria Brasileira, 2014)
Measurements of the phosphate adsorption/desorption characteristic of three acid soils from Southern Bahia, Brazil, were compared with other soil properties and with the response of sorghum to a range of phosphate additions. One soil (Tropudult Camacã), containing smectite and with a high content of exalate-extractable (amorphus) Fe and Al oxides, showed high phosphate adsorption and provided the test plants with a good supply of phosphate. A contrasting soil (Haplorthox crystalino) showed lower phosphate adsorption, lower phosphate availability, and gave a high phosphate immobilization. It contained high amounts of Fe and Al extractable by dithionite; gibbsite and goethite were identified. The half-life of labile phosphate in this soil was 170, 210 and 275 days measured by phosphate uptake by sorghum plants, isotopic exchange, and anion-resin extraction, respectively. ln the other two soils the half-life was over 400 days by all three methods. Anion-exchange resin extraction provided a convenient index of labile phosphate, and hence of immobilization of phosphate. The contrasting behaviour of the soils shows that adsorption and immobilization of phosphate need to be distinguished: a high adsorption coefficient does not necessarily mean high immobilization.